Cirugía metabólica: ¿una nueva alternativa para el tratamiento de la diabetes mellitus tipo 2? - Lanzarini S., Enrique; Csendes J., Attila; Lembach, Hanns; Molina Y., Juan Carlos; Papapietro V., Karin; Araya Q., Verónica (Revista Hospital Clínico Universidad de Chile, 2010)
Type 2 Diabetes Mellitus is a global epidemic. Classical studies have demonstrated the benefits of tight glycemic control, showing a decrease in complications and mortality. Current therapy based on changes in lifestyle and medication accomplishes these goals in an insufficient number of patients. Follow up of obese patients undergoing bariatric surgery has shown us a significant reduction in overweight and control comorbidities. In diabetic patients, there is adequate glycemic control, decreased insulin resistance, and decrease in glycosylated hemoglobin. The pathophysiological mechanisms that explain these effects are being studied, and includesbenefits associated with significant and sustained weight loss, and mechanisms independent of weight loss that appear early after surgery. The latter would be due to changes in GI anatomy induced by surgery, including activation of the entero insular axis, exclusion of the foregut, and stimulation of the distal ileum with enhanced incretin production. Since the surgery seems to have an effect on diabetes that is primary, specific and independent of weight loss, authors have suggested de idea of extending surgical indication to diabetic patients with BMI <35. Initial surgical experience in this group of patients show encouraging results, however, at this point there is insufficient data to generalize its indication. The results of ongoing surgical protocols will help to clarify the role of surgery in the treatment of Type 2 Diabetes in patients with BMI <35.